2022
DOI: 10.1186/s42155-022-00286-2
|View full text |Cite
|
Sign up to set email alerts
|

STABILISE; treatment of aortic dissection, a single Centre experience

Abstract: Purpose To outline the process of the STABILISE technique and its use; reporting patient outcomes and midterm follow up for complicated aortic dissection. Materials and methods Single centre retrospective analysis from January 2011 to January 2021 using the STABILISE technique which utilises balloon assistance to facilitate intimal disruption and promote aortic relamination. Results Sixteen patients un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…In this statement, endovascular treatment of TAAD was not formally endorsed due to scarcity of high-quality cumulative data [8]. The present systematic review addresses this gap in the literature and constitutes the most comprehensive synopsis of TAAD management with TEVAR to date [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. Herein, mean patient age at the time of intervention was 60.7 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this statement, endovascular treatment of TAAD was not formally endorsed due to scarcity of high-quality cumulative data [8]. The present systematic review addresses this gap in the literature and constitutes the most comprehensive synopsis of TAAD management with TEVAR to date [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. Herein, mean patient age at the time of intervention was 60.7 years.…”
Section: Discussionmentioning
confidence: 99%
“…Data regarding the timing of TAAD were available in 16/20 studies [26][27][28]31,33,34,[36][37][38][39][40][41][42][43][44][45]. In total, 72.00% (95% CI, 52.45-88.64%) of our cohort suffered from acute TAAD (<14 days), 4.12% (95% CI, 0.00-19.19%) had subacute TAAD (15-90 days), while chronic dissection (>90 days) was present in 12.75% (95% CI, 2.24-47.09%) of the reported patients.…”
Section: Disease and Peri-operative Detailsmentioning
confidence: 99%
“…Through our case analysis and literature review, it has been observed that the prevailing diagnostic model for arteriovenous malformation primarily relies on the presence of positive FAST, abdominal pain, imaging evidence of fluid accumulation, and a reduction in hemoglobin levels, all of which collectively indicate the likelihood of AVM occurrence. CT angiography (CTA) may have false negative results, however, due to short acquisition times when bleeding is not obvious at time of scan [ 20 ]. It has been described that transcatheter arterial embolization is a definitive treatment [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…34 The device has not gained widespread use but established the feasibility of balloon membrane rupture to eliminate the false lumen, a technique that would be subsequently modified by others to achieve more complete treatment of TBAD using the STABILISE technique. [35][36][37][38][39][40][41][42][43][44][45][46][47]…”
Section: Techniques To Prevent Aneurysmal Degeneration Of Tbad Knicke...mentioning
confidence: 99%
“…58 Others have reported similar results in both the acute and chronic setting using the STABILISE teichnique. 35,37,39,43,59,60 Some have recommended more aggressive use of distal stenting and endografting in the infrarenal and iliac segments to cover all identifiable reentry tears. These reports suggest improved remodeling of the abdominal aortoiliac segment at the potential expense of increased SCI.…”
Section: Stabilise Techniquementioning
confidence: 99%